FINANCIAL DUE DILIGENCE AKUISISI CITIBANK N.A., INDONESIA OLEH PT BANK UOB INDONESIA - Sharon Wong; Destya Wiranata; Angelique Jocelyn; Natasya Mintarja; Nanik Linawati (MANAJEMEN DEWANTARA, 2025)
This study aims to explain the changes in profitability and compare the company value of Citibank, N.A., Indonesia before and after being acquired by PT Bank UOB Indonesia and to see financial due diligence and whether PT Bank UOB has done the right strategy. Profitability is measured by the ratio of Net Profit Margin, Return On Equity, and Return On Asset. The research method used is a quantitative approach with a comparative research type. The result of this study is that after the acquisition in 2022 there was a significant decrease in 2024 in Net Profit Margin (NPM) between before the acquisition and after the acquisition, besides that there was a decrease in Return On Assets (ROA) and also Return On Equity (ROE). Therefore, no financial synergy exists through the acquisition of Citibank, N.A., Indonesia by PT Bank UOB Indonesia.